Sulfur Synergy: Improving Black Soybean (Glycine max (L.) Merrill) Yields with Varied Sources and Levels - , Anki Mibang, Kasinam Doruk, Sanchung Lida, Karge Basar, Nabam Akli, Karthikeyan M (Archives of Current Research International, 2024)
Field experiment was laid out at agriculture field of Himalayan university, Jollang during Kharif season 2023-2024 to study the response of black soybean to levels and sources of sulphur under mid - hill conditions of Arunachal Pradesh. The treatments comprising of all possible combinations of three levels of sulphur viz. 15, 30 and 45 kg /ha and four sources of sulphur viz. Iron pyrite, Gypsum, Epsom salt and Sphalerite. The result revealed that yield attributes viz. number of pods per plant, number of seeds per pod, seed weight, seed yield, biological yield and harvest index of black soybean increased with the application of S upto 45 kg/ha. Higher dose of sulphur significantly influence yield attributes of black soybean. The response per kg S apply was 14.5 kg of soybean grain. Among the sources of sulphur gypsum gave the better response in terms of yield attributes and seed and straw yield of soybean over the other sources. Gross returns (27322 ₹/ha), net returns (12552 ₹/ha) and B: C (1.84) ratio was significantly higher at Gypsum 45 kg S/ha.